2022
DOI: 10.3390/agronomy12123185
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspective of Medicinal Mushroom Cultivations: A Review Case for ‘Magic’ Mushrooms

Abstract: Fruiting bodies, mycelia, or spores in the form of extracts or powder of various medicinal mushrooms are used to prevent, treat, or cure a range of ailments and balance a healthy diet. Medicinal mushrooms are found in several genera of fungi and their fruit bodies, cultured mycelia, and cultured broth contains phytochemical constituents such as triterpenes, lectins, steroids, phenols, polyphenols, lactones, statins, alkaloids, and antibiotics. Edible mushrooms are considered functional foods that can be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The class of polyphenols known as flavonoids can also be present on mushrooms, at quantities of up to 3.0 mg per gram of dried matter. Homogentisic acid, benzoic acid (4-OH-benzoic, vanillic, protocatechuic, salicylic) and cinnamic acid derivatives (caffeic, ferulic, p-coumaric, myricetin and catechin) are some of the principal flavonoids reported in mushroom species [96]. However, some researchers affirm that edible mushrooms lack the enzymes necessary for synthesizing flavonoids, and studies have not found significant flavonoid absorption in cultivated fruiting bodies or mycelia grown in flavonoid-rich environments.…”
Section: Phenols and Polyphenols From Mushroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The class of polyphenols known as flavonoids can also be present on mushrooms, at quantities of up to 3.0 mg per gram of dried matter. Homogentisic acid, benzoic acid (4-OH-benzoic, vanillic, protocatechuic, salicylic) and cinnamic acid derivatives (caffeic, ferulic, p-coumaric, myricetin and catechin) are some of the principal flavonoids reported in mushroom species [96]. However, some researchers affirm that edible mushrooms lack the enzymes necessary for synthesizing flavonoids, and studies have not found significant flavonoid absorption in cultivated fruiting bodies or mycelia grown in flavonoid-rich environments.…”
Section: Phenols and Polyphenols From Mushroomsmentioning
confidence: 99%
“…Numerous terpenes and terpenoids (terpenes with the addition of functional groups, usually oxygen-containing) can be obtained from medicinal mushrooms, and are responsible for their antioxidant, anti-inflammatory, anticancer activities, and immunomodulatory [96]. The mushroom extracts from Hypsizygus tessullatus (brown and white varieties) and Flammulina velutipes, for example, showed good antiproliferative activities against human breast cancer cell lines (CF-7 and MDA-MB-231 cell lines).…”
Section: Phenols and Polyphenols From Mushroomsmentioning
confidence: 99%
“…Moreover, Sommano et al [27] presented novel perspectives on cultivating medicinal mushrooms. The fruiting bodies, mycelium, or spores in the form of extracts or powders of various medicinal mushrooms are used to prevent or treat many ailments and to balance a healthy diet.…”
Section: Yield and Quality Of Aromatic Plantmentioning
confidence: 99%
“…К продуцентам микробных ферментов относят различные виды бактерий и грибов. В последнее время перспективными продуцентами протеолитических ферментов являются высшие базидиальные грибы (отдел Basidiomycоta), токсикологическая безопасность которых подтверждена Всемирной организацией здравоохранения [4]. Известно, что к этому отделу относятся грибы, разрушающие растительные субстраты.…”
Section: Introductionunclassified